2021
DOI: 10.1109/jlt.2021.3078508
|View full text |Cite
|
Sign up to set email alerts
|

Widely Tunable RF Signal Generation Using an InP/Si3N4 Hybrid Integrated Dual-Wavelength Optical Heterodyne Source

Abstract: Photonics-based techniques spearhead the generation of high-frequency signals in the millimeter-andTerahertz wave, crucial for ultrabroadband mobile wireless link development. Photonic integration is enabling to provide the photonic approach with added advantages of energy-efficiency, flexibility and scalability, in addition to signal quality. We present an optical heterodyne system based on a novel dual laser module containing two InP-Si 3 N 4 hybrid lasers with intracavity wavelength selective optical filter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…1 shows the hybrid circuit forming the dual-laser source. This source has been previously used for free-running mm-wave generation [3] and optical transmission [13]. Since both lasers in the PIC are identical, only the locking characteristics of laser 1 were measured.…”
Section: A Device Structurementioning
confidence: 99%
See 1 more Smart Citation
“…1 shows the hybrid circuit forming the dual-laser source. This source has been previously used for free-running mm-wave generation [3] and optical transmission [13]. Since both lasers in the PIC are identical, only the locking characteristics of laser 1 were measured.…”
Section: A Device Structurementioning
confidence: 99%
“…A microwave photonics application that has been recently explored in this hybrid platform is mm-wave heterodyne generation [3]. Recent works integrating two InP-Si 3 N 4 lasers on the same chip have shown that, while the two lasers can have very low intrinsic linewidth, the RF beatnote still exhibits a long-term drift due to thermal instabilities [3]. This drift can hinder the use of such a solution on any telecom system due to failing to comply with current regulations on frequency stability [4].…”
mentioning
confidence: 99%
“…Naturally, photonic integrated circuits (PICs) appear to be the ideal option to overcome these issues, especially considering the recent boom of generic foundry platforms [7], [8], [9]. Integrating distinct lasers on the same chip and then merging their beams is a straightforward solution [10], [11], [12], [13], [14] but the absence of coupling between the different wavelengths prevent their use in some applications, such as two-color self-mixing velocimetry for which the mode competition represent a key element [15]. Moreover, the phase noises for each laser are uncorrelated and therefore adds up which can be an important drawback [16].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we demonstrate an optical heterodyne A-RoF system with a dual tunable hybrid integrated InP-SiN laser module and simplified system architecture incorporating a single ended modulator, a single optical amplifier and an envelope detector. Based on the use of integrated micro-ring resonators (MRRs) the dual laser module has been shown to be tunable over the entire C band [10] and can be fine-tuned to achieve desired carrier frequency spacings -offering continuous RF carrier tuning from 5 GHz to 150 GHz when used in a heterodyne configuration [11]. More details of the laser module and system are discussed in section II.…”
Section: Introductionmentioning
confidence: 99%